Endogenous fluctuations and the role of monetary policy - Mordecai Kurz; Hehui Jin; Maurizio Motolese (Fondazione Eni Enrico Mattei (FEEM), 2002)
This paper studies the dynamic volatility properties of a monetary economy in which agents hold Rational Beliefs (see Kurz (1994), (1997)) rather than Rational Expectations. Except for this feature the examined Rational Belief Equilibrium (in short, RBE) is entirely standard: markets are competitive, prices are flexible and all information is symmetric. The paper demonstrates a) The RBE paradigm offers an integrated theory of real and financial volatility with a high volume of trade. Most volatility in an RBE is induced endogenously through the beliefs of agents.b) Although our RBE assumes fully competitive markets in which prices are fully flexible,the diverse expectations of agents can explain most of the familiar features of monetary equilibria. This includes, money non-neutrality, Phillips curve and impulse response functions with respectto monetary shocks.c) Agents with diverse but inconsistent beliefs may induce socially undesirable excess fluctuations even when the allocation is ex-ante Pareto optimal. Central bank policy should aim to reduce the endogenous component of this volatility.
Keywords: 330; Konjunkturtheorie; Rationale Erwartung; Geldpolitik